Influence of Ocean Circulation and Benthic Exchange on Deep Northwest Atlantic Nd Isotope Records During the Past 30, 000 Years. (13th September 2019) - Pöppelmeier, F.; Blaser, P.; Gutjahr, M.; Süfke, F.; Thornalley, D. J. R.; Grützner, J.; Jakob, K. A.; Link, J. M.; Szidat, S.; Lippold, J.
Abstract: Neodymium (Nd) isotopes extracted from authigenic sediment phases are increasingly used as a proxy for past variations in water mass provenance. To better constrain the controls of water mass provenance and nonconservative effects on the archived Nd isotope signal, we present a new depth transect of Nd isotope reconstructions from the Blake Bahama Outer Ridge along the North American continental margin covering the past 30 ka. We investigated five sediment cores that lie directly within the main flow path of the Deep Western Boundary Current, a major advection route of North Atlantic Deep Water. We found offsets between core tops and seawater Nd isotopic compositions that are observed elsewhere in the Northwest Atlantic. A possible explanation for this is the earlier suggested redistribution of sediment by nepheloid layers at intermediate as well as abyssal depths, transporting material downslope and along the continental margin. These processes potentially contributed to Nd isotope excursions recorded in Northwest Atlantic sediment cores during the Bølling‐Allerød and early Holocene. An Atlantic‐wide comparison of Nd isotope records shows that the early Holocene excursions had an additional contribution from conservative advection of unradiogenic dissolved Nd. Nevertheless, the trends of the Nd isotope records are in general agreement with previous reconstructions of water mass provenance from the entire Atlantic and also reveal millennial‐scale changes during the last deglaciation in temporal high resolution, which have rarely been reported before. Further, the new records confirm that during cold periods the Northwest Atlantic was bathed by an increased contribution of southern sourced water. Plain Language Summary: The Atlantic Meridional Overturning Circulation is of great importance for the climate system since it distributes heat to the northern high latitudes, where the only deep water of the Northern Hemisphere is formed. Here, we investigate how this North Atlantic Deep Water propagated southward in response to deglacial climatic trends during the transition from the last ice age to modern day. However, we found differences between the archived modern signal and modern seawater measurements that might hinder the interpretation of past water mass provenance. We attribute this effect to influences from suspended material altering the local bottom waters. This process was likely most prominent during the invigoration of northern deep water formation during the Bølling‐Allerød and early Holocene but less pronounced to absent during cold time periods. Nevertheless, the findings of this study confirm that North Atlantic Deep Water was partly replaced in the deep Northwest Atlantic basin by southern sourced water during cold intervals. Key Points: Sedimentary archives indicate alteration of local bottom water Nd isotope signatures in the Northwest Atlantic by nepheloid layers New high‐resolution Nd isotope depth transect from the Blake Bahama Outer Ridge constrains deglacial millennial‐scale water mass changes An increased contribution of southern sourced water is confirmed for all cold periods of the past 30 ka